If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(t + 1) = 5 Reorder the terms: -5(1 + t) = 5 (1 * -5 + t * -5) = 5 (-5 + -5t) = 5 Solving -5 + -5t = 5 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -5t = 5 + 5 Combine like terms: -5 + 5 = 0 0 + -5t = 5 + 5 -5t = 5 + 5 Combine like terms: 5 + 5 = 10 -5t = 10 Divide each side by '-5'. t = -2 Simplifying t = -2
| 13=-3x | | x^4-x^2=12 | | 1=24x | | 11x+2-10x=-14 | | 4a^2-12a+9=4 | | 12x^3y-75xy^3= | | 5x-5y=-9 | | 2*(2x)+10=3x+13 | | -5x+2y=11 | | -10x=-10 | | x+8=2x-10 | | 27x=-1 | | 14=2x-9 | | 32=2x-10 | | 20u+18v= | | 5y^2-33y-14=0 | | -8x=-2 | | x^2-2x-36=0 | | 0.25x-14.8= | | 10x=42 | | 9x=-8 | | v(10)-v(3)= | | -6X+4=7X+121 | | 5x-7(0)=-18 | | k=0 | | 5(0)-7y=-18 | | 7X+1=121-5X | | (q^2+5q+4)(q^2-1)+q^3-q=2q+2q^2-2 | | -4X+10=21+7X | | 3x-6(0)=-7 | | 3(0)-6y=-7 | | 2=-1x+45-8 |